The Bliss Institute, cultural centre in the heart of Belize City - Government Information Service (The Angelus Press, Belize City, British Honduras, C.A. Printed in U.S.A., 2009)
The Bliss Institute is the home for the Performing Arts in Belize and hosts the artworks of many Belizean artists. It is also a venue for theatre performances and film festivals.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Belize; Buildings--Belize; Cultural property--Belize; Architecture--Belize